Mapping of QTL in the Mutus#1 wheat line resistant to leaf spot - Sánchez-Vidaña, Mariel del Rosario; Vargas-Hernández, Mateo; He, Xinyao; Paola Sansaloni, Carolina; Kumar-Singh, Pawan; Hernández-Anguiano, Ana María (Revista Mexicana de Ciencias Agrícolas, 2022)
Wheat leaf spot caused by Zymoseptoria tritici is a devastating disease in wheat cultivation internationally. Chemical control and the use of resistant varieties are the main control strategies. The International Maize and Wheat Improvement Center (CIMMYT) has wheat lines with quantitative resistance to the disease, so the objective was to map quantitative trait loci (QTL) associated with genetic resistance to leaf spot in the elite line Mutus#1 (resistant), in a population of 275 recombinant inbred lines (RILs) derived from the cross of Mutus#1 with the elite line Huirivis#1 (susceptible). In 2018 and 2019, a field experiment was established at the CIMMYT-Toluca station under an Alpha Lattice experimental design. An artificial epidemic was generated with Z. tritici and the area under the disease progress curve (AUDPC) was calculated. The 275 RILs and parents were sequenced using the DArTSeq platform. The linkage maps were constructed with the IciMapping program using phenotype and genotype information. Five minor-effect QTLs were identified, three located on chromosomes 1B, 4A and 4B and two on chromosome 5B, which explained less of the symptoms and production of pycnidia in adult plants carried by Mutus#1, they can be used with other resistance genes or QTLs to reduce the selection of new pathogenic strains of Z. tritici.
Keywords: Mycosphaerella graminicola; Triticum aestivum; Zymoseptoria tritici